2020
DOI: 10.51248/.v40i3.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Swiss ball exercise and Pilates exercise on core muscle strengthening in college cricketers

Abstract: Introduction and Aim: Cricket is one of the most popular game in India played by men and women of all ages. Core stability is defined as the ability to control the position and movement of the trunk over the pelvis to allow optimum production, transfer and control of force and movement to the terminal segment. Major muscles involved are pelvic floor muscles, Transverse abdominis, multifidus, internal and external obliques, and rectus abdominis. Core is used to stabilize the thorax and the pelvis during dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Performing strength exercises on Swiss ball has been pushed on the conviction that a labile surface will give a greater challenge to trunk musculature, increment the dynamic balance and potentially trains to balance out their spine to prevent and treat injury 7 . Kamatchi K (2020) suggested that the majority of the research work done on abdominal muscle exercise were comparing them with traditional mat exercises, and the benefits of Swiss ball exercise appear to have been applied to whole body exercise equally 15 . Swiss ball is a type of therapeutic tool, which is used to improve the muscle tone, balance, control, structure and coordination of the movement achieving a greater activation of musculature 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Performing strength exercises on Swiss ball has been pushed on the conviction that a labile surface will give a greater challenge to trunk musculature, increment the dynamic balance and potentially trains to balance out their spine to prevent and treat injury 7 . Kamatchi K (2020) suggested that the majority of the research work done on abdominal muscle exercise were comparing them with traditional mat exercises, and the benefits of Swiss ball exercise appear to have been applied to whole body exercise equally 15 . Swiss ball is a type of therapeutic tool, which is used to improve the muscle tone, balance, control, structure and coordination of the movement achieving a greater activation of musculature 15 .…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1) The results of this study are in accordance to the previous study in which Pilates improved core strength and enhance the physical performance of cricketers. 1 And the good core strength improved agility and speed in athlete. 16 In another study significant improvement was observed in agility and speed of running in male cricket players which is in coherence with the results of recent study in which agility and ground fielding improved significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid such complications, athlete must have strong core musculature, and endurance. 1,4,5 The core contains the muscles of pelvis and trunk which provides stability. 6 Thus strengthening of core musculature is important to avoid injuries in cricketers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations